2014
DOI: 10.3390/ijerph110908645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Metabolic Parameters in Non-Small Cell Lung Carcinoma and Colorectal Cancer Patients with and without KRAS Mutations

Abstract: Lung cancer (LC) and colorectal cancer (CRC) are the first and second deadliest types of cancer worldwide. EGFR-based therapy has been used in the treatment of these cancers with variable success. Presence of mutations in the KRAS driver oncogene, possibly induced by environmental factors such as carcinogens in diet and cigarette smoke, may confer worse prognosis and resistance to treatment for reasons not fully understood. Data on possible associations between KRAS mutational status and clinical and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…First, other blood-routine markers such as mean platelet volume are unavailable in this study. It is widely reorganized that mean platelet volume is superior over platelet count as a marker of platelet function and activation [ 46 , 47 ]. Second, the findings presented in this study cannot be directly extrapolated to the general populations as we only enrolled postoperative patients for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First, other blood-routine markers such as mean platelet volume are unavailable in this study. It is widely reorganized that mean platelet volume is superior over platelet count as a marker of platelet function and activation [ 46 , 47 ]. Second, the findings presented in this study cannot be directly extrapolated to the general populations as we only enrolled postoperative patients for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating association between obesity/MetS and KRAS status have yielded inconclusive results [14][15][16][17][18]. In this study we investigated associations between serum lipid profile, BMI and metabolic factors with KRAS status according to primary tumour location.…”
Section: Discussionmentioning
confidence: 94%
“…Associations between environmental factors and KRAS status have not been extensively investigated. Only a few studies have reported inconsistent findings regarding associations between BMI/metabolic parameters and KRAS status [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The currently available EGFR-targeted drugs, including EGFR-tyrosine kinase inhibitors and monoclonal antibodies, can augment the activities of corresponding inhibitors and the susceptibility to gefitinib. 24 …”
Section: Discussionmentioning
confidence: 99%